GEOMETRIC SEQUENCE IN CHEMISTRY - KLEPANCOVA, Michaela (Trends in education, 2015)
The contribution states multiple examples of geometric sequence in chemistry. The main focus was finding of such samples of utilization of knowledge about the concept of secondary school mathematics that will lead to the finding of results or relations with immediate application in chemistry.
Keywords: geometric sequence; application; chemistry.